2022
DOI: 10.48550/arxiv.2201.05607
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Response approach to the integrated shear 3-point correlation function: the impact of baryonic effects on small scales

Anik Halder,
Alexandre Barreira

Abstract: The integrated shear 3-point correlation function 𝜁 Β± is a higher-order statistic of the cosmic shear field that describes the modulation of the 2-point correlation function πœ‰ Β± by long-wavelength features in the field. Here, we introduce a new theoretical model to calculate 𝜁 Β± that is accurate on small angular scales, and that allows to take baryonic feedback effects into account. Our model builds on the realization that the small-scale 𝜁 Β± is dominated by the nonlinear matter bispectrum in the squeezed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…However, it has been found that these statistics do not capture all the information from the non-linear and non-Gaussian regime of the WL field. This has led to an array of work attempting to extract this additional information, including non-Gaussian 𝑁-point statistics such as the 3-point function and its Fourier transform the angular bispectrum (Fu et al 2014;Coulton et al 2019;Halder et al 2021;Halder & Barreira 2022), Minkowski functionals (Maturi et al 2010;Munshi et al 2011;Kratochvil et al 2012;Petri et al 2013;Marques et al 2019;Gatti et al 2021), convergence peak and minima statistics (Jain & Van Waerbeke 2000;Yang et al 2011;Liu et al 2015;Kacprzak et al 2016;Li et al 2019;Martinet et al 2021;ZΓΌrcher et al 2021;Harnois-DΓ©raps et al 2021), as well as machine learning methods (Gupta et al 2018;Fluri et al 2019;Ribli et al 2019;Matilla et al 2020;) and related techniques (Cheng et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been found that these statistics do not capture all the information from the non-linear and non-Gaussian regime of the WL field. This has led to an array of work attempting to extract this additional information, including non-Gaussian 𝑁-point statistics such as the 3-point function and its Fourier transform the angular bispectrum (Fu et al 2014;Coulton et al 2019;Halder et al 2021;Halder & Barreira 2022), Minkowski functionals (Maturi et al 2010;Munshi et al 2011;Kratochvil et al 2012;Petri et al 2013;Marques et al 2019;Gatti et al 2021), convergence peak and minima statistics (Jain & Van Waerbeke 2000;Yang et al 2011;Liu et al 2015;Kacprzak et al 2016;Li et al 2019;Martinet et al 2021;ZΓΌrcher et al 2021;Harnois-DΓ©raps et al 2021), as well as machine learning methods (Gupta et al 2018;Fluri et al 2019;Ribli et al 2019;Matilla et al 2020;) and related techniques (Cheng et al 2020).…”
Section: Introductionmentioning
confidence: 99%